The use of VIKOR method in finding the optimal solution for a specialpurpose geodetic network design - Anđić, Darko (Geodetski vestnik, 2023)
This study deals with the use of VIKOR method in finding the optimal solution for a special-purpose geodetic network design. It is about a multi-criteria compromise ranking method developed in 1986. Based on previously defined criteria functions related to precision and reliability, four acceptable alternative solutions were firstly established. Then, with the aim of finding the optimal one, those solutions were subjected to VIKOR method. The geodetic micro-network used in this study was simulated as a trilateration one and consisted of six control points discretizing a structural geometry as well as four, five or six reference points (pillars), depending on what alternative solution it was about. The optimal network design should have ensured the detection of deviations of the control points' positions in accordance with a priori introduced tolerances and constraints. It turned out the approach based on VIKOR method is a very efficient tool in tasks involving multiple conflicting requirements referred to a geodetic engineer and in the cases when the decision must be made in a short term.
Keywords: alternative network design solutions; alternativne rešitve zasnove mreže; metoda VIKOR; multicriteria compromise ranking; namenska geodetska mreža; natančnost; optimal network design; optimalna zasnova mreže; precision; reliability; special-purpose geodetic network; tolerance; tolerances; večkriterijska kompromisna lestvica; VIKOR metho; zanesljivost